Characteristics and Outcome of Diffuse Large B-Cell Lymphoma in Hepatitis C Virus–Positive Patients in LNH 93 and LNH 98 Groupe d'Etude des Lymphomes de l'Adulte Programs - Besson, Caroline; Canioni, Danielle; Lepage, Eric; Pol, Stanislas; Morel, Pierre; Lederlin, Pierre; Van Hoof, Achiel; Tilly, Hervé; Gaulard, Philippe; Coiffier, Bertrand; Gisselbrecht, Christian; Brousse, Nicole; et al. (Journal of clinical oncology, 2006)
Epidemiologic studies show an association between hepatitis C virus (HCV) and B-cell non-Hodgkin's lymphoma (NHL). Treatment and outcome of patients with diffuse large-cell lymphoma (DLCL) and HCV infection are still a matter of debate. We studied the HCV-positive patients with B-cell DLCL included in the Groupe d'Etude des Lymphomes de l'Adulte (GELA) programs LNH 93 and LNH 98. They were compared with the other patients with DLCL included in these programs. HCV infection prevalence was 0.5% (26 of 5,586 patients). Histologic types of HCV-positive DLCL were more frequently transformed from low-grade lymphoma than DLCL in HCV-negative patients (32% v 6%, P = .02). This is also supported by more frequent spleen involvement in HCV-positive patients (46% v 17%, P < .001). HCV-positive patients had more frequently elevated lactate dehydrogenase levels than other patients (77% v 55%, P = .02). Outcome of HCV-positive patients was poorer for overall survival (P = .02) but not for event-free survival (P = .13). After matching on age and prognosis factors, at 2 years of follow-up, the overall survival was 56% (95% CI, 33% to 76%) among HCV-positive patients, versus 80% (70% to 89%), and the event-free survival was 53% (33% to 72%) versus 74% (64% to 84%). The short-term hepatic toxicity of chemotherapy was strongly increased among HCV-positive patients. After exclusion of the two subjects with chronic hepatitis B virus infection, the overall proportion of subjects undergoing hepatic toxicity was 65% (15 of 23 patients). HCV-positive patients with DLCL differ from other patients both at presentation and during chemotherapy. Specific protocols evaluating antiviral therapy should be designed for these patients.